Effect of service quality, company image, and customer satisfaction in Word Of Mouth - Melastri, Komang; Giantari, I.G.A.K. (International research journal of management, IT and social sciences, 2019)
The sample of this study was 155 respondents, taken using the Random Sampling technique, with the criteria that respondents were attending an English Language Business English program at EF Denpasar, and education at least graduated from high school or equivalent. The results of the study show that (1) Service quality has a positive and significant effect on customer satisfaction. (2) The company's image has a positive and significant effect on customer satisfaction. (3) Service quality has a positive and significant effect on WOM (Word of Mouth), (4) Company image has a positive and not significant effect on WOM and (5) Customer satisfaction has a positive and significant effect on WOM managerial implications and suggestions for increasing EF English First Denpasar WOM, by increasing customer satisfaction and service quality. Customer satisfaction is enhanced by improving the company's image and increasing the professionalism of EF English First Denpasar teachers.